Science, politics and society in early nineteenth-century Ireland : the Reverend William Richardson - Blackstock, Allan (Manchester University Press, 2013)
Based on newly unearthed source material, this book follows the career of clergyman William Richardsona and assesses his impact on politics, science and agriculture nationally and internationally.
Keywords: Richardson, William, -- 1740-1820 -- Influence.; Richardson, William, -- 1740-1820 -- Political and social views.; Richardson, William, -- 1740-1820.; Richardson, William, -- 1740-1820; Agricultural innovations -- Ireland -- History -- 19th century.; Science -- Ireland -- History -- 19th century.; Ireland -- Politics and government -- 1760-1820.; Agriculture -- Innovations -- Irlande -- Histoire -- 19e siècle.; Sciences -- Irlande -- Histoire -- 19e siècle.; Irlande -- Politique et gouvernement -- 1760-1820.; HISTORY -- Europe -- Great Britain.; HISTORY -- Europe -- France.; Agricultural innovations; Influence (Literary, artistic, etc.); Political and social views; Politics and government; Science; Ireland; 1760-1899; History